Dual Antiplatelet Therapy vs. Single Antiplatelet Therapy After Transcatheter Aortic Valve Replacement: An Updated Systematic Review and Meta-Analysis - Zhang, Yipeng; Shen, Lan; Yang, Wentao; He, Ben (Frontiers in Cardiovascular Medicine, 2021)
Background: Although mainstream guidelines recommend dual antiplatelet therapy (DAPT) with aspirin and clopidogrel in patients following transcatheter aortic valve replacement (TAVR), it is not evidence-based. We aim to investigate the safety and efficacy of DAPT versus single antiplatelet therapy (SAPT) after TAVR with updated evidence reviewed. Methods: We systematically searched PubMed, Embase, and Cochrane for studies comparing DAPT to SAPT after TAVR from inception to Nov 30, 2020. The primary outcome was major adverse cardiac and cerebrovascular events, including allcause mortality, cardiovascular death, myocardial infarction (MI), stroke, and major or life-threatening bleeding (LTB). Subgroup analysis was performed according to study type (randomized control trials vs. observational studies) using a fixed-effects model. The quality of evidence was assessed by two scoring systems and GRADE (Grading of Recommendations Assessment, Development, and Evaluation). Results: Twelve studies of 20766 patients were included in our meta-analysis. Compared with SAPT, DAPT was associated with an increased risk for combined life threatening and major bleeding (OR 1.73 [1.19-2.51], p = 0.004) after TAVR. Such difference was largely driven by major bleeding (OR 2.29 [1.68-3.11], p < 0.001). There were no significant differences on major adverse cardiovascular events (MACE) (OR 1.19 [0.99-1.44], p = 0.07), cardiovascular mortality (OR 1.46, [0.93-2.30], p = 0.10), and stroke (OR 0.97, [0.80-1.16], p = 0.71). Conclusions: Compared with SAPT, Post-TAVR DAPT was associated with increased risks of major or life-threatening bleeding without additional benefits of reducing thrombotic events. Future guidelines of post-TAVR antiplatelet strategy are expected to be updated as new high-quality evidence emerges.